The Shifting Romance with Israel - Gannon, Ray. (Shippensburg : Destiny Image, Inc., 2012)
Linking Pentecostals and Jews. An intellectual discussion about the fraternal twin movements: Zionism and American Pentecostalism. Everyone interested in Israel and its relationships with religious groups in the United States will be enthralled with this thoroughly researched and thoughtfully presented examination of two world-changing movements. Shifting Romance with Israel is an intellectual discussion about the fraternal twin movements: Zionism and American Pentecostalism, birthed at the beginning of the 20th century. Both newborns, initially treated as weak and infantile in a religiously h.
FOREWORD; PREFACE; INTRODUCTION; Chapter 1 THE HISTORICAL SOURCES FOR THE PETECOSTAL IDEOLOGY OF ISRAEL; Chapter 2 FRATERNAL TWIN INFANTS; Chapter 3 CLASSICAL PENTECOSTALISM'S ROMANTIC IDEOLOGY OF ZIONISM (1918-1945); Chapter 4 PENTECOSTAL IDEOLOGICAL CONDEMNATION OF ANTI-SEMITISM; Chapter 5 PENTECOSTALISM'S IDEOLOGY OF MESSIANIC ZIONISM (1946-1972); Chapter 6 PENTECOSTALISM'S ROMANTIC BREAKUP WITH ISRAEL; Epilogue THE EVERLASTING BOND BETWEEN CLASSICAL PENTECOSTALISM AND THE JEWISH STATE; GLOSSARY; ENDNOTES.
Description based on print version record.
Keywords: Protestantism and Zionism; Pentecostal churches -- Relations -- Israel; Israel -- Relations -- Pentecostal churches; POLITICAL SCIENCE / Essays; POLITICAL SCIENCE / Government / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Reference; Electronic books